REKONSEPTUALISASI ASAS DEMOKRASI EKONOMI DALAM KONSTITUSI INDONESIA - Reka Dewantara (Arena Hukum, 2014)
AbstractEconomic democratic principles as a basis for the formulation of economic regulation in the national economy plays a role in strengthening democratic governance and steering regulator goes into the national economy. Government is not stable, in the sense that is able to distribute the rights and obligations of each economy in a fair economy, then the economy is genuinely democratic will not be realized. In the State of Indonesia shows the process of democratization that took a half-hearted and not shown in a positive direction for strengthening governance. Economic reforms needed in Indonesia is reforming its economic system, namely the renewal rules are likely to seek welfare rules only become better ensure economic justice through increased equitable distribution of development outcomes according to the concept of social economy. Results interpretation of economic and legal experts as the economy that is democratic, then the implementation of best practices in system or economic system should be more democratic with the full participation of the people. The results show the concept of economic democracy principles in Article 33 paragraph (4) NRI Know 1945 Constitution explicitly that the obligation can be analyzed in the operational structure of institutional economics views of business ownership shall be fairly based on the constitution. Countries represented the State Owned Enterprises (SOEs) and the Regional Owned Enterprises (enterprises) is the main implementing actors are given the authority to manage the vital sectors in the economy that controls the lives of many people in accordance with Article 33 of the constitution. This indicates the importance of strengthening state institutions in managing the resources of nature, especially that dominate the lives of many people, so it is not depend on foreign capital.  Key words: reconceptualization, economic democracy, constitution  AbstrakAzas demokrasi ekonomi sebagai dasar perumusan regulasi di bidang perekonomian nasional berperan dalam penguatan pemerintahan demokratis yang menjadi pengatur dan pengarah berjalannya ekonomi nasional. Pemerintahan yang belum stabil, dalam artian mampu mendistribusikan hak dan kewajiban ekonomi masing-masing ekonomi secara adil, maka ekonomi yang benar-benar demokratis tidak akan dapat terwujud. Di Negara Indonesia saat ini menunjukkan proses demokratisasi yang berlangsung setengah hati dan belum  menunjukkan arah yang positif bagi penguatan pemerintahan. Reformasi di bidang ekonomi yang diperlukan Indonesia adalah reformasi dalam sistem ekonominya, yaitu pembaharuan aturan main yang cenderung mencari kesejahteraan semata menjadi aturan main yang lebih menjamin keadilan ekonomi melalui peningkatan pemerataan hasil-hasil pembangunan sesuai konsep ekonomi sosial. Hasil interpretasi dari para ahli ekonomi dan hukum sebagai perekonomian yang bersifat kerakyatan, maka pelaksanaan sistem atau best practices dalam sistem ekonomi harus lebih demokratis dengan partisipasi penuh dari rakyat. Hasil penelitian menunjukkan  konsep asas demokrasi ekonomi di dalam Pasal 33 ayat (4) UUD NRI Tahu 1945 secara eksplisit dapat dianalisis bahwa adanya kewajiban dalam operasional struktur kelembagaan ekonomi dilihat dari kepemilikan usaha diatur secara adil berdasarkan konstitusi. Negara yang diwakili Badan Usaha Milik Negara (BUMN) maupun Badan Usaha Milik Daerah (BUMD) merupakan actor pelaksana utama  yang diberikan kewenangan untuk mengelola sektor-sektor vital dalam perekonomian yang menguasai hajat hidup orang banyak sesuai Pasal 33 konstitusi. Hal ini mengindikasikan pentingnya penguatan institusi negara dalam mengelola sumber-sumber  kekayaan alam terutama yang menguasai hajat hidup orang banyak, sehingga tidak tergantung pada modal asing. Kata kunci: rekonseptualisasi, azas demokrasi ekonomi, konstitusi